The Cross-Cultural Adjustment of Hotel Expatriates in Malaysia the Mediating Effects of Comunication and Interaction - Haslina, Halim (2013)
Despite the abundance of research in the area of expatriation, the growth of hotel industry and the increase in the number of people serving abroad in the industry, there remains a relative lack of empirical research investigating the mediating effects of variables such as communication and interaction on expatriate adjustment. Therefore, the main purpose of this study is to investigate the mediating effects of communication and interaction in the adjustment of hotel expatriates in Malaysia. The study also investigates differences in the patterns of adjustment between organizational expatriates (OEs) and self-initiated expatriates (SIEs). Besides, relationships between individual, organizational and nonwork factors and expatriate adjustment are determined and the most influential predictors of expatriate adjustment are also identified. The U-Curve Theory and Social Learning Theory guided this thesis, which used a survey to measure the attitudes and opinions of the 203 respondents comprised of expatriates working in the Malaysian hotel industry. Multiple statistical tests were used to analyze data and ensure the reliability and validity of the instruments. Results revealed that communication and interaction partially mediated the relationships between individual, organizational and nonwork variables and expatriate adjustment. The results also showed that OEs and SIEs in the hotel industry did not differ significantly in their adjustment but there were significant differences in the pattern of adjustment of expatriates from different regions. Previous international experience, social support and family adjustment showed significant positive relationships with expatriate adjustment. Meanwhile, social support and family adjustment were the most influential predictors of expatriate adjustment. The findings are significant for the industry and also contributed to new empirical findings to the literature on expatriation and cross-cultural adjustment.